2014
DOI: 10.1097/qad.0000000000000261
|View full text |Cite
|
Sign up to set email alerts
|

Drug resistance among newly diagnosed HIV-infected children in the era of more efficacious antiretroviral prophylaxis

Abstract: Background In the era of more efficacious prevention of mother-to-child transmission (PMTCT) regimens, documenting the profile of drug resistance in HIV-infected infants and young children is critical to our efforts to improve care and treatment for children. Methods HIV drug resistance mutations in plasma virus were ascertained using population sequencing among 230 newly-diagnosed HIV-infected children under 2 years of age recruited in Johannesburg, South Africa, during 2011. By this time, more effective PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
70
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 14 publications
7
70
1
Order By: Relevance
“…Onethird of the children had no exposure to PMTCT. However, 24.0 % were detected to have resistance to NNRTI, NRTI in 10.7 % and PI in 1.3 % [27]. Shao et al [28] carried out a study to determine DRM among children under 18 months born to HIV-1-infected mothers who accessed PMTCT services in northern Tanzania.…”
Section: Prevalence and Different Types Of Drug Resistance Mutationsmentioning
confidence: 98%
See 1 more Smart Citation
“…Onethird of the children had no exposure to PMTCT. However, 24.0 % were detected to have resistance to NNRTI, NRTI in 10.7 % and PI in 1.3 % [27]. Shao et al [28] carried out a study to determine DRM among children under 18 months born to HIV-1-infected mothers who accessed PMTCT services in northern Tanzania.…”
Section: Prevalence and Different Types Of Drug Resistance Mutationsmentioning
confidence: 98%
“…This is also consistent with the evidence that knowledge of patient's virus resistance profile prior to treatment will go a long way to avoid unnecessary stopping of a particular regimen and switching to others regimens. The cohorts showed resistance across the main ARV classes although in varying degrees [15,18,22,[24][25][26][27][28][29][30][31].…”
Section: Prevalence and Different Types Of Drug Resistance Mutationsmentioning
confidence: 99%
“…New pediatric HIV infections have declined dramatically; however, children who acquire HIV often do so while exposed to antiretroviral drugs. The development of antiretroviral drug resistance with failed PMTCT is well documented in the setting of "single-dose" nevirapine (NVP) for PMTCT [5][6][7]; however, similar complications may occur with continuous infant nevirapine prophylaxis or maternal ART [8][9][10]. Ongoing work is needed to optimize pediatric ART, to ensure that the regimens offered are effective and durable over time.…”
mentioning
confidence: 99%
“…A recently published prospective observational study from South Africa demonstrated a high prevalence of NNRTI resistance (52%) among infants who fail HIV-prophylaxis [29]. In another study from South Africa conducted in 2011, 56.8% of HIV-1-infected children harbored NNRTI, 14.8% harbored NRTI, and 1.3% harbored PI mutations [3]. Since a relevant percentage of new HIV-1-infected children seen at our center are immigrants from sub-Saharan Africa, this selection of DRMs being reported might have an impact on the prevalence of DRMs in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The use of ART in pregnancy and as prophylaxis in infants for the prevention of mother-to-child transmission (MTCT) has led to a pronounced reduction of vertical HIV-1 transmission, but a selection of drug-resistant mutations (DRMs) in infected infants is increasingly being reported [3,4]. Some HIV-1 subtypes and recombinants seem to accelerate the emergence of DRMs [4,5].…”
Section: Introductionmentioning
confidence: 99%